A Study on DSLM Transporting the Rare Earth Metal La (III) with a Carrier of PC-88A. (7th June 2018) - Lu, Shibao; Wang, Yan; Pei, Liang; Li, Wei
Abstract : This paper studies transmission behavior of La (III) in dispersed supported liquid membrane (DSLM) of dispersed phase constituted by dispersed supported liquid membrane solution and HCl solution with polyvinylidene fluoride membrane (PVDF) as support and kerosene as membrane solvent, with 2-ethyl hexyl phosphonic acid-single-2-ethyl hexyl ester (PC-88A) and two-(2-ethyl hexyl) phosphoric acid (D2EHPA) as mobile carrier. It also investigates the influence of La (III) transmission by the material liquid acidity, initial concentration of La (III), HCI concentration, membrane solution, and HCI solution volume ratio, resolving agent and carrier concentration, as well as concluding that the optimal transmission and separation conditions are dispersed phase of 4.00 mol/L HCl concentration, 30:30 volume ratio of membrane solution, and HCl solution, within 0.160 mol/L controlled carrier concentration and 4.00 pH value of material liquid. Under the optimal conditions, the La (III) initial concentration of material liquid phase is 8.00× 10–5 mol/L mol/L, 125 min, and 93.9% migration rate. Under the condition of unchanged acidity of resolving phase, HCL, H2 SO4, and HNO3 as resolving agent, at 125th min, the migration rates of La (III) are 93.9%, 94.0%, and 87.8%, respectively. HCl solution, H2 SO4 solution, and HNO3 solution have a certain effect on the La (III) resolution, of which 4.00 mol/L HCl solution and 2.00 mol/L H2 SO4 solution are better. The effect of HNO3 is slightly lower than HCl and H2 SO4 .